ANALISIS STANDAR PELAYANAN MINIMAL PADA INSTALASI RAWAT JALAN DI RSUD KOTA SEMARANG - Sinta Indi Astuti; Septo Pawelas Arso; Putri Asmita Wigati (Jurnal Kesehatan Masyarakat (Undip), 2015)
In order to improve the quality of hospital services in Indonesia, one of the government's efforts is to engage a system for the Public Service Board (PSB). RSUD Semarang that has changed its status to become Regional Public Service Board (RPSB) in 2007 have an obligation to implement the Minimum Service Standards (MSS) in their service but until now RSUD Semarang have never assessing SPM on the outpatient Installation so it is necessary to investigate the SPM monitoring and compliance efforts at the outpatient installation in RSUD Semarang. The method used is qualitative method with cross sectional approach, analysis of data using content analysis. From the survey results revealed that the monitoring in fulfillment of MSS at outpatient installation in RSUD Semarang has not gone well and also the SPM evaluation and assessment has not been carried out. For the indicator at a specialist clinic providers already met supported by the specialist in accordance with the specialty. Indicator of the availability of the service has been fulfilled which medical personnel, administrative personnel and other health facilities are already available. Indicator of the opening hours of service have not been met due to delays in the arrival of the doctor because of their visit schedule is at the same time with the opening hours of outpatient, so doctors come late to outpatient polyclinic. Indicators of service waiting time is unmet because the doctor came in late for reason above, the shortage of specialist doctor where the number of specialist doctor in some clinic only one person so that when that doctor performed emergency measures then the outpatient patient cannot be serviced. The delay of medical record file delivery due to the narrowness of the patient's medical record file storage area and the lack of human resources in outpatient registers lead the search process of old patient files become slowly. Indicator of customer satisfaction is unmet because of the long waiting time and inhospitable nurses, but it is also due to the lounge facilities are less comfortable and less clean toilets. Indicator of TB diagnosis enforcement through microscopic examination and recording, reporting of TB cases are met with the facilities and capabilities of the laboratory personnel, in addition, also because of the availability of a complete TB form and laptops provided by the Department of Health to assist the process of TB recording and reporting. Suggestions that need to be done to evaluate MSS periodically, adding space and patients file storage rack, improve hospitality personnel, increasing the number of specialists, make regulations in doing visit hours and practice hours of polyclinic doctor.